PROSPEK DAN TANTANGAN DESENTRALISASI PENDIDIKAN DI KALIMANTAN TIMUR - Mariman Darto (Pusjar SKPP Lembaga Administrasi Negara, 2005)
The decentralization of educational functions is one of crucial issues in the current era. The practice of centralized education management in the previous period constituted the main obstacle in recuperating educational quality nation-wide, and simultaneously, has tended to weaken the capacity of local government. In line with the policy of extended decentralization, most of education authorities are supposed to be reassigned to the District/City Government, or even to the school. It is believed to be the best way to generate the following advantages: improving decision-making process; promoting education management based on local content and local characteristics; and empowering the potency of local people. As one of the richest provinces in Indonesia, East Kalimantan Province is demanded to realize such education reform. The main challenge is how to strengthen the role of education in budding quality, relevance, management efficiency, and equity of education access for all community members. How does East Kalimantan Province implement such challenges, and what does decentralization of educational functions look like? This paper tries to scrutinize those queries.